The Psychological Impacts of Hybrid Work Arrangements: a Systematic Review - Opie Oktavia I. Simanjuntak; Wiwin Hendriani (EduInovasi: Journal of Basic Educational Studies, 2025)
The global work paradigm transformation accelerated by the COVID-19 pandemic has resulted in massive adoption of hybrid work arrangements with diverse and contradictory psychological impact findings. This research aims to systematically identify and analyze the psychological impacts of hybrid work arrangements based on current literature synthesis.  The study employed a qualitative approach using systematic literature review method adopting thematic synthesis framework, analyzing 10 high-quality journals through PRISMA methodology from PubMed, PsycINFO, Web of Science, Scopus, and Google Scholar databases for the 2020-2025 period. Findings revealed ambivalent psychological impacts, with benefits including increased work engagement, work-life balance, and job satisfaction, but also challenges of social isolation, boundary ambiguity, and career development barriers. Effectiveness was influenced by complex moderating factors including work modalities, individual characteristics, and organizational support through Job Demands-Resources model and Conservation of Resources theory mechanisms. Hybrid work arrangements require a holistic approach that considers psychological risk factors by developing comprehensive mitigation strategies to maintain mental well-being while maximizing the benefits of work flexibility.